2008
DOI: 10.1179/174313208x362479
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal death after peripheral nerve injury and experimental strategies for neuroprotection

Abstract: The future of peripheral nerve repair lies in modulating neurobiology at the time of injury, repair and during regeneration. Neuroprotection may be an essential component of that therapeutic package.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 155 publications
1
65
0
Order By: Relevance
“…Following nerve crush in adult rats, regenerating whisker afferents are first observed within the whisker follicle at 2 wk, but this reinnervation is delayed by several more weeks with nerve transection without repair (Renehan and Munger 1986). These findings suggest that the surgical procedures for repair used in the present study facilitate more rapid recovery of peripheral nerve function, although available evidence indicates that to be effective, such repair must be performed soon after the injury (Faroni et al 2015;Hart et al 2008). …”
Section: Discussionmentioning
confidence: 40%
“…Following nerve crush in adult rats, regenerating whisker afferents are first observed within the whisker follicle at 2 wk, but this reinnervation is delayed by several more weeks with nerve transection without repair (Renehan and Munger 1986). These findings suggest that the surgical procedures for repair used in the present study facilitate more rapid recovery of peripheral nerve function, although available evidence indicates that to be effective, such repair must be performed soon after the injury (Faroni et al 2015;Hart et al 2008). …”
Section: Discussionmentioning
confidence: 40%
“…This suggests that the stem cells might enhance motor neuron regeneration to a greater extent than sensory neurons. A number of studies have shown that peripheral nerve axotomy leads to DRG sensory neuron cell death [58,59]. In this study, we found that using stimulated human ASC, we were able to reduce the expression levels of caspase-3, an important mediator of apoptosis, suggesting that cell transplantation could provide a neuroprotective effect in addition to boosting regeneration.…”
Section: Stimulated Asc Enhance Nerve Repairmentioning
confidence: 51%
“…Unlike peripheral nerves, cauda equina nerve roots lack perineurium to hold the injured end together during attempts were made to suture it. 4 The epidural anaesthesia is given to the space around the dura and vertebral canal at a desired site in such a way that the anaesthetic fluid diffuses through the dural sheath and the nerve gets anaesthetised. The diameter invest the cauda equina as a sac-like structure and loosely invest the structures and subarachnoid space is ballooned out to form lumbar cistern.…”
Section: Discussionmentioning
confidence: 99%